Transient Characteristics of Confined Submerjed Laminar Jet Impingement Heat Transfer from a Vibrating Heater - Sridhar, Abishek; Narayanaswamy, Ramesh; Narayanan, V. (Indian Institute of Technology Madras, 2011)
This paper presents the results of an investigation on the effects of applied surface-vibrations on forced convective heat transfer due to a confined submerged impinging two-dimensional laminar air-jet, for different nozzle-to-heater distances. A new dimensionless parameter representing the frequency of applied vibration is introduced. A comprehensive understanding of the effect applied surface vibrations for non-dimensional nozzle-to-heater distances of H = 1 & 8 is delineated with a parametric study for non-dimensional amplitudes of A = 0.05 & 0.2 and non-dimensional frequency of vibrations in the range 0 ≤ F ≤ 12.8, for a fixed jet Reynolds number of 500. Both instantaneous and time-averaged characteristics of flow and heat transfer are discussed, along with graphical results. It was found that the effect of surface vibrations were larger for smaller values of H, for any given values of other controlling parameters.